PENGARUH KUALITAS LAYANAN PENGADAIAN SYARIAH TERHADAP LOYALITAS NASABAH DI KOTA MAKASSAR - Suarni, Agusdiwana; Kasim, Muhammad Najib; Febriana, Asna (Jurnal Ilmiah Al-Tsarwah, 2023)
Pegadaian Syariah is a formal financial institution in charge of distributing financing in the form of providing loan money to people in need, based on sharia pawning law, is something that needs to get a positive response. In sharia pawning, the most important thing is to keep away from the practices of usury, speculation and Gharar, which result in injustice and injustice to the community and customers. The purpose of this study is a type of quantitative research with the aim of knowing the effect of the quality of sharia pawnshop services on customer loyalty in the city of Makassar. This sample was taken from the customers of Pawnshop Syariah Central Makassar as many as 69 respondents. The type of data used in this study is quantitative data obtained from questionnaires distributed and associated with the problem under study. The research instrument used in this study used the Likert scale method. Based on the results of data research using statistical calculations through the application of the Statistical Package for the Social Science (SPSS) version 26. Based on the partial calculation results, the service quality variable is not significant to the customer loyalty variable, which is indicated by the value of 0.885 which is greater than 0.05 with the T test value showing 0.146. This means that the service quality variable has a positive but not significant effect on customer loyalty at Pegadaian Syariah Makassar City. The service at the Makassar Central Sharia Pawnshop is quite satisfactory even though it does not really affect customer loyalty, but is influenced by other variables.